2021
DOI: 10.1007/s41999-021-00546-9
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of 27,049 polytraumatized patients age 60 and above: identifying changes over 16 years

Abstract: Purpose The number of severely injured patients exceeding the age of 60 has shown a steep increase within the last decades. These patients present with numerous co-morbidities, polypharmacy, and increased frailty requiring an adjusted treatment approach. In this study, we establish an overview of changes we observed in demographics of older severe trauma patients from 2002 to 2017. Methods A descriptive analysis of the data from the TraumaRegister DGU® (TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
2
9
0
1
Order By: Relevance
“…Older trauma patients are now more numerous than younger adults, which is also consistent with reported international information 2,3,21−27 . Our results also con rm previous ndings that falls are the most common injury mechanism among older adults 28,29 . Falls are also very prevalent in younger adults as they have interchangeably been the leading cause of trauma with MVC in that population.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Older trauma patients are now more numerous than younger adults, which is also consistent with reported international information 2,3,21−27 . Our results also con rm previous ndings that falls are the most common injury mechanism among older adults 28,29 . Falls are also very prevalent in younger adults as they have interchangeably been the leading cause of trauma with MVC in that population.…”
Section: Discussionsupporting
confidence: 92%
“…An Australian study reported a signi cant increase in the population-adjusted incidence of thoracic injury (8%/year), with the greatest increase being in patients aged ≥ 85 years (14%/year) 30 . Other authors also reported an increasing number of older adults with spine injuries 29 . which are mostly the result of low-energy trauma and predominantly affect the axial cervical spine.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Die Größe, das Gewicht, das Alter und Vorerkrankungen haben ebenfalls einen Einfluss auf das Verletzungsmuster des Patienten nach einem traumatischen Ereignis. Besonders bei älteren Patienten (> 60 Jahre) ist nach einem Hochrasanztrauma mit Komplikationen zu rechnen, die häufig durch Vorerkrankungen, Einnahme verschiedener Medikamente (Polypharmazie) und Gebrechlichkeit (Frailty) begründet sind [6,7,12,15,16].…”
Section: Patientenklassenunclassified